1997
DOI: 10.1046/j.1365-3156.1997.d01-184.x
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide prevalence study of hypertension and related non‐communicable diseases in The Gambia

Abstract: SummaryThe prevalence of hypertension, diabetes and obesity in The Gambia was assessed in a 1% population sample of 6048 adults over 15 years of age. 572 (9.5%) subjects were hypertensive according to WHO criteria (a diastolic blood pressure (DBP) of 95 mmHg or above and/or a systolic blood pressure (SBP) of 160 mmHg or above); 325 (5.4%) had a DBP of 95 mmHg or above, and 39 (2.3%) a DBP of 105 mmHg or above; 428 (7.1%) had a SBP of 160 mmHg or above. By less conservative criteria (a DBP of 90 mmHg or above a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
3
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 26 publications
6
59
3
1
Order By: Relevance
“…4 Other studies from sSA have observed variation in prevalence of hypertension between urban and rural communities, but our studies show such variation also exists within rural communities, as seven out of the nine 'high prevalence' and 10 out of the 18 'low prevalence' communities were rural. From a public health, preventive point of view, modification of risk factors at population level is likely to be the most cost-effective approach with the highest impact on morbidity.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…4 Other studies from sSA have observed variation in prevalence of hypertension between urban and rural communities, but our studies show such variation also exists within rural communities, as seven out of the nine 'high prevalence' and 10 out of the 18 'low prevalence' communities were rural. From a public health, preventive point of view, modification of risk factors at population level is likely to be the most cost-effective approach with the highest impact on morbidity.…”
Section: Discussioncontrasting
confidence: 61%
“…4 The objective of the present study was to determine if such a high degree of geographical variation in the prevalence of hypertension could be confirmed. If confirmed, this would suggest novel opportunities for control strategies and future research; while estimates of geographical variation between communities are essential in the design and analysis of CRTs.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In a previous nationwide rapid assessment we found that 9.5% of adults above the age of 15 had a BP у160/95 mm Hg. 17 The aim of the present study was to assess in more detail BP patterns, and to investigate the prevalence of hypertension and other cardiovascular risk factors in rural and urban settings in The Gambia.…”
Section: Introductionmentioning
confidence: 99%